PENGARUH KONSELING KARIER TERHADAP PENINGKATAN EFIKASI DIRI PADA SISWA SMP 12 BANJARMASIN - Dina Aprilia (Faculty of Ushuluddin and Humanities, 2013)
This study is aimed at determining the effect of career counselling on increasing self efficacy among Junior High School Students. To find the effect, this study investigates two group of students. The first group is those who got the conselling career, while the second group did not. The result is that those who got conselling career have higher self efficacy than those who did not. This means that career counselling truly increases self efficacy in career making decision among the students.